Teachers’ role in online learning: Perspectives of prospective Indonesian EFL teachers - Christiani, Natalia; Tungka, Novalita Fransisca; Nainggolan, Romauli (Journal of Education and e-Learning Research, 2023)
This study investigated how prospective English as a foreign language teachers perceived the role of their teachers in online learning and how those roles contributed to their experiences in a low-tech online learning context. This study surveyed 285 prospective teachers at seven universities across provinces with English Language Education programs in Indonesia (East Java, North Sumatera, Central Sulawesi, West Kalimantan, West Papua, East Nusa Tenggara and Bali) and interviewed 10 prospective teachers to provide a deeper understanding of their experiences. The results showed that the cognitive role is the most important teacher role perceived by prospective teachers in a low-tech online learning context. Three themes emerged from the results: the teacher’s cognitive sub-roles in providing learning assistance and recommendation, managerial sub-roles in leading, controlling and organizing the learning process and affective sub-roles in creating an enjoyable, relaxing learning environment and catching students’ attention in online learning. The discussion focuses on the different effects of the roles on creating a positive online learning environment for students. In conclusion, teaching skills related to the three roles of teachers in online learning must be taught explicitly in a teacher-training program through scenario-based learning activities. The implications of teacher-training programs are discussed further in this paper.